War Through an Interdisciplinary Lens. Book Review of ‘An Inquiry into the Applied Theory of War’ by Andrey A. Kokoshin - V. A. Zolotarev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The book under review is a new seminal work by Andrey A. Kokoshin, the 6th Secretary of the Security Council of the Russian Federation and a member of the Russian Academy of Sciences. The monograph explores a wide range of applied and theoretical aspects of war and peace problematique. The reviewer emphasizes a profundity of Kokoshin’s analysis — based on a careful examination of classical works on the art of war as well as contemporary studies by the leading military theorists — and his interdisciplinary approach. In particular, the reviewer stresses that the author considers both objective and subjective factors when addressing such issues as the impact of technological parameters on modern warfare, hybrid wars and deterrence. The reviewer also commends the author’s observations on new trends in modern warfare, including an increase in number and geographical scope of local military conflicts, a worldwide growth in military expenditures, and an explosive progress in advanced military technologies. Andrey A. Kokoshin emphasizes that studying classics of military sciences can help understand these trends and develop optimum responses to the correspondent national security challenges. The reviewer concludes that the book under review represents an important contribution to the theoretical studies of war as a specific political and social phenomenon and expresses the hope that its publication will provide a new impetus to the advancement of Russian military thought.